Frecuencia de aislamiento de Streptococcus β – hemolítico de secreción faríngea en estudiantes de la escuela de Microbiología y Parasitología de la Universidad Nacional de Trujillo. Trujillo – Perú, 2017 - Avalos Luciano, Lucia Del Carmen (2017)
Bacterial pharyngitis due to β - hemolytic Streptococcus is a pathology of medical importance. Human beings constitute the natural reservoir of group A, C and G Streptococcus; Which are considered producers of pharyngitis that are transmitted from person to person by respiratory route. The present study aimed to evaluate the frequency of isolation of β - hemolytic Streptococcus in students of the School of Microbiology and Parasitology of the National University of Trujillo, from January to March, 2017._x000D_ The number of samples consisted of pharyngeal secretions of 82 students belonging to the School of Microbiology and Parasitology of the National University of Trujillo, which were inoculated in Thioglycolate fluid and seeded by the streak technique in blood agar, incubated at 37 ° C for a period of 24 to 48 hours, obtaining small, pointy, translucent and betahemolytic colonies that are compatible with the Streptococcus genus, these were planted in BHI broth and incubated at 37 ° C for 24 hours, Gram staining With coconuts being observed in chains and sowing in blood agar to obtain the pure culture. For the presumptive identification of β - hemolytic Streptococcus the pure cultures were used, to which the catalase test was performed and the sensitivity was Bacitracin and Trimetropin - Sulfamethoxazole. With the use of Bacitracin and Trimetropin - Sulfamethoxazole discs, the presence of β - hemolytic Streptococcus from group A and group from A._x000D_ In conclusion, the frequency of isolation of β - hemolytic Streptococcus is 21%, in addition it was found that group A - hemolytic Streptococcus is in a higher percentage (59%) than non - hemolytic β - hemolytic Streptococcus (41 %)